2010
DOI: 10.2139/ssrn.1616546
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Systems: Efficiency and Institutions

Abstract: This paper presents a set of indicators to assess health care system performance. It also presents new comparative data on health care policies and institutions for OECD countries. This set of indicators allows the empirical characterisation of health care systems and the identification of groups of countries sharing similar health institutions. It also helps to uncover strengths and weaknesses of each country's health care system and assessing the scope for improving value-for-money. The empirical analysis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
219
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(234 citation statements)
references
References 63 publications
1
219
0
9
Order By: Relevance
“…Turning to the link between spending and health outcomes (e.g. life expectancy, mortality), the empirical evidence is so far inconclusive about the strength of the link between health care spending and health outcomes (Martin et al, 2008;Joumard et al, 2010). This is partly because other factors such as life-style, diet and environment are perceived as key factors determining health outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Turning to the link between spending and health outcomes (e.g. life expectancy, mortality), the empirical evidence is so far inconclusive about the strength of the link between health care spending and health outcomes (Martin et al, 2008;Joumard et al, 2010). This is partly because other factors such as life-style, diet and environment are perceived as key factors determining health outcomes.…”
mentioning
confidence: 99%
“…On balance, research has shown that no health care system performs systematically better in delivering cost-effective health care. Rather it is how the system is managed that matters for effective outcomes (Joumard et al, 2010).…”
mentioning
confidence: 99%
“…Several studies have confirmed that there is a positive relationship between life expectancy at birth and health expenditure per capita worldwide [6][7][8]. A recent study by Joumard [9] in 2010 showed that an increase of total health spending is the possible reason for at least 40% of improvements in life expectancy since 1990. So, this fact should be considered that health spending is necessary for analyzing any public health achievements cross-countries.…”
Section: Introductionmentioning
confidence: 94%
“…This paper applies DEA to a sample of OECD countries, for which the quality of production factors is expected to be more homogeneous and measurement errors possibly less pronounced. As such, the paper places itself in a stream of previous OECD studies (Sutherland et al, 2007;Joumard et al, 2010;Hribernik and Kierzenkowski, 2013), of which it represents an update. Following Hribernik and Kierzenkowski (2013), efficiency is assessed with reference to spending on health care, secondary education and general public administration.…”
Section: Data Envelopment Analysismentioning
confidence: 99%